Identification of prognostic hypoxia-related genes signature on the tumor microenvironment in esophageal cancer - Linlin Tan (AIMS Press, 2021)
Background: Hypoxia is a crucial factor in the development of esophageal cancer. The relationship between hypoxia and immune status in the esophageal cancer microenvironment is becoming increasingly important in clinical practice. This study aims to clarify and investigate the possible connection between immunotherapy and hypoxia in esophageal cancer.